2018
DOI: 10.3389/fpsyt.2018.00698
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Personality Disorder and Its Association With Methamphetamine Dependence in Compulsory Treatment Facilities in China

Abstract: Methamphetamine use is popular and rapidly increasing in China, and the co-occurrence of personality disorders has an impact on treatment outcomes and may increase vulnerability of developing dependence. The aim of the present study was to investigate the prevalence rates of personality disorders in methamphetamine users and further explore the association between personality disorders and methamphetamine use status. Five hundred and seventy-seven male methamphetamine users were recruited. The self-developed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Another study reported an association between psychiatric disorders caused by chronic and heavy MA abuse and ASPD 16 . In similar research in China, the occurrence rate of ASPD in MA dependent was 75.5%, significantly higher than the nondependent group (59.9%) 17 . Taken together, these results show a high prevalence rate of ASPD in MA patients.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Another study reported an association between psychiatric disorders caused by chronic and heavy MA abuse and ASPD 16 . In similar research in China, the occurrence rate of ASPD in MA dependent was 75.5%, significantly higher than the nondependent group (59.9%) 17 . Taken together, these results show a high prevalence rate of ASPD in MA patients.…”
Section: Introductionsupporting
confidence: 54%
“…16 In similar research in China, the occurrence rate of ASPD in MA dependent was 75.5%, significantly higher than the nondependent group (59.9%). 17 Taken together, these results show a high prevalence rate of ASPD in MA patients.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Approximately one in five people with bipolar disorder is also diagnosed with borderline or emotionally unstable PD [13], affective and anxiety disorders are strongly associated with schizotypal PD [14], and the prevalence rate of PDs in individuals at high risk for psychosis has been found to be as high as 39% [15]. There is also a well-known relationship between PDs and substance use disorder (SUD) [16][17][18][19][20][21][22][23][24]. A clinical study from Denmark found comorbid SUD in 39% of patients with PDs [16], and a systematic review from 2000 estimates that 38-57% of patients with borderline PD have at least one SUD diagnosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Two hundred and seven male MA abusers, with an MA abuse frequency of ≥10 times and an MA abuse duration of ≥1 year from 577 volunteer participants of Xinkaipu Compulsory Rehabilitation Institute (Changsha, Hunan) and White Mud Lake Compulsory Rehabilitation Institute (Xiangyin, Hunan), underwent a Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I/P) from March 2013 to January 2014. Compulsory rehabilitation is the primary form of treatment for illegal drug dependence (61.6% drug users received compulsory treatment by 2012) in China (21). The residential MA users were admitted in the treatment facilities after confirmed MA use by urine or hair test.…”
Section: Participantsmentioning
confidence: 99%